Analisis Pelaksanaan Pelayanan Perizinan Pada Dinas Penanaman Modal Dan Pelayanan Satu Pintu Kabupaten Bengkalis - Yeni Mayasari; Rosmayani Rosmayani; Lilis Suriani (UIR Press, 2021)
The purpose of this study was to analyze the implementation of services to manage building permits (IMB) in the Department of Investment and One Stop Services (DPMPSP) Bengkalis Regency. The method in this research uses quantitative descriptive research which means to describe and explain in depth the public services that are carried out. Technical data collection using observation, interviews, documentation and questionnaires. Based on the research findings, it can be concluded that the mechanism and procedures for implementing the services provided to the community have met the standard service procedures. The service period is fast and continues to be maximized by service officers and technical officers involved in issuing building permits. Service fees that are free of charge to license applicants and the payment system most applicants expect through ATMs. Service products that are considered to be very good and also require regular improvement, such as in the product of complaint services. Supporting facilities and infrastructures are deemed necessary for special attention so that the creation of maximum service, although at this time with existing facilities and infrastructure services are still carried out to the maximum. The competency of service officers is also maximized by providing soft skills and hard skills training, especially in building permit services.